Hearing function and thresholds: a genome-wide association study in European isolated populations identifies new loci and pathways. Issue 6 (14th April 2011) - Girotto, Giorgia; Pirastu, Nicola; Sorice, Rossella; Biino, Ginevra; Campbell, Harry; d'Adamo, Adamo P; Hastie, Nicholas D; Nutile, Teresa; Polasek, Ozren; Portas, Laura; Rudan, Igor; Ulivi, Sheila; et al.
Abstract : Background: Hearing is a complex trait, but until now only a few genes are known to contribute to variability of this process. In order to discover genes and pathways that underlie auditory function, a genome-wide association study was carried out within the International Consortium G-EAR. Methods: Meta-analysis of genome-wide association study's data from six isolated populations of European ancestry for an overall number of 3417 individuals. Results: Eight suggestive significant loci (p<10 −7 ) were detected with a series of genes expressed within the inner ear such as: DCLK1, PTPRD, GRM8, CMIP . Additional biological candidates marked by a single nucleotide polymorphism (SNP) with a suggestive association (p<10 −6 ) were identified, as well as loci encompassing 'gene desert regions'—genes of unknown function or genes whose function has not be linked to hearing so far. Some of these new loci map to already known hereditary hearing loss loci whose genes still need to be identified. Data have also been used to construct a highly significant 'in silico' pathway for hearing function characterised by a network of 49 genes, 34 of which are certainly expressed in the ear. Conclusion: These results provide new insights into the molecular basis of hearing function and may suggest new targets for hearing impairment treatment and prevention.